Appropriating Me. A New Emerging Aesthetic in the Indian Diaspora of South Africa - Nalini Moodley (IAFOR Journal of Cultural Studies)
This article aims to examine the production, consumption and interpretation of visual texts that were generated from within the Indian diaspora of South Africa. These images are located in and engaged with through social and popular media that democratise access to these visual texts. Within this diasporic community, the desire for the imaginary of home is foregrounded and explicated through the types, styles and discourse emerging within this community. This paper presents a critical analysis of three case studies: a suit of garments, a film franchise, and a body of artificially generated visual art. Using an insider’s reflexivity and a postcolonial framework, this ethnographic inquiry explores the critical interweaving of identity construction, appropriation, and the development of a new aesthetic. This research, located within the body of Cultural Studies, frames, and deepens an understanding of cultural appropriation as a socio-political phenomenon. The study offers a new form of appropriation submitted as mypropriation, where the creator appropriates from inside their own community, religion, tradition or culture as they exist “inside”: thus, an intra-community appropriation. This form of appropriation leads to a new Paavam aesthetic that creates space for creative works that celebrate history, culture and traditions of diasporic communities through an internalised view of the authentic. While diasporas are considered deterritorialised, this aesthetic reinscribes an identity of ownership in navigating the complexities in moving from the periphery to the centre. This study finds that as a conceptual framework, paavam practices are complex and contradictory and could frame how diasporic communities envision their narratives.